The Implementation of Guided Inquiry in the Learning Subject of Virus Based on Multiple Representations toward Students’ Critical Thinking - Rahmawati, Ain Amalia; Mubarok, Ibnul (Journal of Biology Education, 2021)
Biology is a subject that involves the scientific process in its teaching and learning activity so that it requires a learning model which can apply that scientific process, one of which is guided inquiry. The learning subject of virus is abstract, cannot be seen directly in everyday life and is microscopic in nature within which requires visual presence, not only verbal explanation so that students can fulfil their basic competence, namely analyzing (C4) which is included in the category of high-level thinking. In the learning model implemented at SMA N 1 Lasem, the teacher has not yet developed students’ critical thinking skills. One of the learning models that can be applied to improve critical thinking skills is guided inquiry based on multiple representations. The aim of this research is to determine the effectiveness of the implementation of guided inquiry in the learning subject of virus based on multiple representations toward students’ critical thinking skills. This research is an experimental research with a pre-test post-test control group design. The sample was class of X MIPA 3 as the experimental class and class of X MIPA 5 as the control class. The researchers used purposive sampling technique. The data collection methods were tests, observations, and questionnaires. The result showed that the average post-test mark of the experimental class was higher than that of the control class; that is 80.1 with classical completeness up to 92% and N-gain of 0.46 categorized as medium in the experimental class, while in the control class, the average post-test mark is 72.5 with a classical completeness of 78% and N-gain of 0.24 categorized as low. These results were strengthened by a questionnaire on students responses, teacher responses and observations of the learning process which gave a positive response with ≥ 75% categorized as good to the guided inquiry learning model based on multiple representations in the learning subject of virus. Based on the results of the research, it can be concluded that the implementation of guided inquiry based on multiple representations in the learning subject of virus is effective in improving students’ critical thinking skills.